2015
DOI: 10.1519/jsc.0000000000000820
|View full text |Cite
|
Sign up to set email alerts
|

Water-Based Concurrent Training Improves Peak Oxygen Uptake, Rate of Force Development, Jump Height, and Neuromuscular Economy in Young Women

Abstract: The study investigated the effects of different intrasession exercise sequences on the cardiorespiratory and neuromuscular adaptations induced by water-based concurrent training in young subjects. Twenty-six healthy young women (25.1 ± 2.9 years) were placed into 2 water-based concurrent training groups: resistance before (RA, n = 13) or after (AR, n = 13) aerobic training. Subjects trained resistance and aerobic training during 12 weeks, 2 times per week performing both exercise types in the same training ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Graef et al (17) found that a program of aquatic exercises with resistance control has the most effective gains in 1RM of adduction/abduction horizontal shoulders. Although they found significant gains in both orders of performing aerobic exercises and resistance (AR vs. RA) within the same exercise session, Pinto et al (27–29) believe that performing strength exercises before aerobic exercises seems to be more effective in the gains of muscle strength compared with the reverse order. Katsura et al (21) found similar responses of strength after performing training with and without resistive devices.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Graef et al (17) found that a program of aquatic exercises with resistance control has the most effective gains in 1RM of adduction/abduction horizontal shoulders. Although they found significant gains in both orders of performing aerobic exercises and resistance (AR vs. RA) within the same exercise session, Pinto et al (27–29) believe that performing strength exercises before aerobic exercises seems to be more effective in the gains of muscle strength compared with the reverse order. Katsura et al (21) found similar responses of strength after performing training with and without resistive devices.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, water has been widely used as a way to increase the resistance to a movement, and strategies such as the use of devices to increase the contact area or buoyancy may require a greater production of strength, generating adjustments in the neuromuscular system. This review found 11 studies that did not use resistance devices (7,10,20,25,(27)(28)(29)(35)(36)(37)40). Of these, only 2 (7,40) found no significant improvements in the parameters of strength, indicating that the use of equipment may not be an indispensable condition for improvement in the neuromuscular system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This article explores the idea that somatic practice encompasses more environments than those aforementioned and specifically addresses the use of water as a new somatic environment. The physical benefits of water exercise to sustain and promote health, wellbeing and conditioning are well known (Buttelli, 2015;Goldstein, 2016;Pinto et al, 2015). Sebastian Kneipp's My Water Cure, published in 1893, examined the healing properties of water therapy and increased its presence in naturopathy (Locher & Pforr, 2007).…”
Section: Introductionmentioning
confidence: 99%